Assessing the Value of Supply Chain Information Sharing in the New Millennium - David A. Marshall (International Journal of Supply Chain Management, 2015)
Information sharing in supply chain management has been studied extensively during the past several years. Many scholars agree that shared information will lead to significant cost savings through inventory and batch size reductions, productivity gains, and other measurables. The purpose of this paper is to review the information sharing related studies in supply chain management research, identify core issues, and offer suggestions for future research. Fifty-five articles were collected from the premier refereed journals in the fields of Supply Chain Management and Operations Management. Classification of the articles based on four common information sharing themes is presented in the paper. A majority of the articles included in this review concentrate on an element of information sharing that leads to strategic changes at the manufacturers and suppliers. Potential future research ideas include additional empirical work and investigation into the leakage effect.